Dynamics of a Modified Sprott A System - Rohman Muhammad Nuur; Tuwankotta Johan Matheus; Harjanto Eric (ITM Web of Conferences)
We examine a modified Sprott A system, one of the 17 chaotic systems without equilibria introduced by Jafari, Sprott, and Golpayegani (2013). For specific parameter values, the modified system exhibits invariant spheres. Using a stereographic map, we analyze the stability of the equilibria and demonstrate that all orbits, except for the unstable equilibrium, converge to the stable equilibrium. For other parameter values, the system has neither invariant spheres nor equilibria. Instead, the state space is foliated by tori.